Exploring student achievement and perceptions in an online flipped grammar course - Ahmad, Djuwairiah; Arifin, Muhammad Ahkam (Universitas Pendidikan Indonesia, 2021)
Flipped learning to date has generally been implemented within a blended classroom. However, the growing number of fully online courses and the existence of Covid-19 have shown the need to try using flipped learning in a fully online class. This paper aimed to explore student achievement and perception in an online flipped grammar class. A paired-sample t-test showed a significant difference between student pre-test and post-test scores with a medium effect size after attending the online flipped course for one month. The interview and questionnaire data revealed students’ overall positive perception toward the introduction of flipped learning within the course. Students mentioned that the flipped approach made the course more interactive and provided them opportunities to ask questions to the teacher with an immediate answer. They also expressed their positive attitude towards the use of different learning platforms (e.g., LMS, Zoom) and modes (synchronous and asynchronous) that could ease their learning experience within the course. Nevertheless, students recommended that the virtual meeting via Zoom needs to be limited in time duration.